A Bilingual Identity-oriented Taxonomy of Nonlinear Dynamic Motivational Strategies - Akbar Bahari (Universitas Ahmad Dahlan, 2020)
To fill the gap of a comprehensive taxonomic framework that includes language and identity-related concepts, a taxonomy of bilingual identities was arranged at psychological, social and cultural levels drawing on Schelling’s Theory of Symbolic Language. The proposed taxonomy enables addressing nonlinearity and dynamicity of L2 motivation by utilizing nonlinear dynamic motivational strategies. Addressing the psychological, social, and cultural dimensions of L2 motivation from a bilingual perspective enables L2 teachers to keep the identified motivational factors in motion regardless of their homogeneity or heterogeneity throughout the learning-teaching process. Addressing the diverse nature of individual learner differences without pushing the learner group toward equal and static performance despite the motivational heterogeneity at the cost of forming a cohesive learner group is the main theoretical implication of the study.